Sun Protection for Your Children - Suzanna Smith (EDIS, 2012)
“My children were all born during the summer months, and as we gradually spent more and more time outside, I wondered how best to protect them from the hot summer sun.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, March 2012.